Design and Build a Chili Sorting Tool Using Color Sensor Based on Arduino Uno - Noviasari, Linda; Asni Tafrikhatin; Khairul Al Bahsyar (Politeknik Piksi Ganesha Indonesia, 2024)
The initial phase of farmers cannot quickly regulate the selection of the quality of produced chili peppers due to limitations in manpower and time. This can lead to inaccuracies in chili selection, resulting in not all marketed chilies being in good condition. The color quality of chili peppers is one of the characteristics that can be observed. Some important factors that also concern chili farmers include the level of chili ripeness, adverse effects on consumers, and a decrease in farmers' or traders' turnover. Based on these problems, researchers developed a design for a chili ripeness sorting tool with a color sensor to sort chili color quality. This research model utilizes Research & Development, with the following stages: potential and problems, information collection, product design planning, product development, product testing, and product revision. The chili ripeness sorting tool based on Arduino Uno utilizes the TCS 3200 color sensor as a device to capture chili color data and a servo motor as an actuator. Based on product testing, the success rate of color readings is 93.33%. This product is expected to assist chili farmers in sorting and determining the quality of chilies to be sold to consumers.